Quality of life of hospitalized patients submitted to hematopoietic stem cells transplantation - Rocha, Vanessa da (2015)
The objective of this study was to assess the quality of life and to identify the altered domains of adult patients with blood cancer, submitted to hematopoietic stem cells transplantation during hospitalization time. A longitudinal, observation and analytical study, conducted in a reference hospital for hematopoietic stem cell transplant. The data collection was during September of 2013 and September of 2014, including 25 patients and using questionnaires for sociodemographic and clinic characteristics, QLQ-C30 and FACT-BMT. A significant statistical worsening (p<0.05) was found in global quality of life, functional scales, physical, social and family function, personal performance, additional worries and symptoms, fatigue, nausea and vomit, pain, loss of appetite and diarrhea. There is impairment in quality of life of patients during hospitalization for the transplantation. This study can subsidize the direction of actions for adequate support during all therapeutic period.